2015
DOI: 10.1016/j.bbabio.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of plastoglobules in thylakoid lipid remodeling during plant development

Abstract: Photosynthesis is the key bioenergetic process taking place in the chloroplast. The components of the photosynthetic machinery are embedded in a highly dynamic matrix, the thylakoid membrane. This membrane has the capacity to adapt during developmental transitions and under stress conditions. The galactolipids are the major polar lipid components of the thylakoid membrane conferring bilayer properties, while neutral thylakoid lipids such as the prenyllipids and carotenoids contribute to essential functions suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 145 publications
(201 reference statements)
4
96
0
8
Order By: Relevance
“…In both chloro- and chromoplasts, CCD4 is one of the major components of plastoglobuli proteomes [137,140], indicating a role for this enzyme in the regulation of carotenoid metabolism in plastid types with marked differences in functionality and carotenoid composition [142]. Moreover, CCD4 protein level is strongly reduced in Arabidopsis mutants defective in the ABC1K1 and ABC1K3 plastoglobuli kinases, suggesting phosphorylation as a post-transcriptional modification necessary for CCD4 protein stability and supporting main activity and localization in plastoglobuli [143].…”
Section: Plant Ccdsmentioning
confidence: 99%
“…In both chloro- and chromoplasts, CCD4 is one of the major components of plastoglobuli proteomes [137,140], indicating a role for this enzyme in the regulation of carotenoid metabolism in plastid types with marked differences in functionality and carotenoid composition [142]. Moreover, CCD4 protein level is strongly reduced in Arabidopsis mutants defective in the ABC1K1 and ABC1K3 plastoglobuli kinases, suggesting phosphorylation as a post-transcriptional modification necessary for CCD4 protein stability and supporting main activity and localization in plastoglobuli [143].…”
Section: Plant Ccdsmentioning
confidence: 99%
“…PG were first thought only to be lipid storage sites. But a series of studies revealed that PG actively participate in lipid synthesis and repair (Eugeni Piller et al, 2012; Rottet et al, 2015; Spicher and Kessler, 2015). It was shown that PG contain enzymes such as tocopherol cyclase (VTE1), NAD(P)H dehydrogenase C1 (NDC1), and phytyl ester synthase (PES), as well as others (Zbierzak et al, 2010; Eugeni Piller et al, 2011, 2014; Lippold et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The current study revealed that α-, β-, γ-, and δ-tocopherol homologs were also present in leaves and stems. Leaves and stems contain chloroplasts, where lipidcontaining thylakoid membranes are found [18][19][20]. This may explain the high levels of lipid-soluble α-tocopherol homologs that are present in leaves and stems.…”
Section: Discussionmentioning
confidence: 95%